Effective early diagnosis for NSCLC: an algorithm. (2nd November 2021) - Zarogoulidis, Paul; Matthaios, Dimitris; Kosmidis, Christoforos; Hohenforst-Schmidt, Wolfgang; Tsakiridis, Kosmas; Mpaka, Sofia; Boukovinas, Ioannis; Drougas, Dimitris; Theofilatou, Vasiliki; Zaric, Bojan; Courcoutsakis, Nikolaos; Nikolaidis, George; et al.
ABSTRACT: Introduction: Lung cancer still remains undiagnosed for most patients until the disease is inoperable. Areas covered: We performed search on PubMed with the keywords: EBUS, radial-EBUS, bronchoscopy, lung cancer, electromagnetic navigation, ct-biopsy, transthoracic biopsy. We present diagnostic equipment and imaging techniques such as positron emission tomography, endoscopical navigation systems, endobronchial ultrasound, radial-endobronchial ultrasound, transthoracic ultrasound biopsy, and computed tomography guided biopsies. Expert opinion: However, lack of early disease symptoms remains the most important issue and therefore we should direct our efforts to screening and early disease diagnosis. An algorithm is proposed for biopsy upon initial disease diagnosis.